Utilization of banana (Musa paradisiaca L.) peel as pectin source as antidiarrheal on castor oil-induced diarrheal Wistar rats model - Martin Adhitya Subagio; Cecilia Noviyanti Salim; Qorina Putri Srisantoso; Yora Nindita; Astika Widy Utomo; Nani Maharani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Banana (Musa paradisiaca L.) peel, locally name pisang raja, contains a high concentration of pectin which is used as antidiarrheal to absorb irritants and increase stool consistency. However, it’s use to increase the stool consistency has not been studied, yet. The study aimed to investigate the effect banana peel extract (BPE) administration on stool consistency of diarrheal rat model. It was an experimental study with a post-test only control group design. Thirty male Wistar rats were induced diarrhea with castor oil and then randomized into five groups. Group I as positive control group was given attapulgite at dose of 124 mg/kg BW. Group II as negative control was given 0.5 mL of 1% tween 80. Group III, IV and V as treatment group were give BPE at different doses of 100, 200 and 400 mg/kg BW, respectively.T he stool consistency was measured every hour for 4 h by weighing fresh and dry stool weight and then the water content was calculated. Data analysis was conducted using one-way ANOVA and LSD post hoc test. Significantly different in stool consistency between Group III, IV, and V compared to Group II (p<0.05) and between groups Group III and IV compare to Group I (p<0.05) were observed. However, there was no significantly different between group V compared to Group I (p=0.149).In conclusion, BPE can increase the stool consistency of castor oil-induced diarrhea rats. The BPE at the dose of 400 mg/kg BW has similar effect to attapulgite.